On the gender effects of handedness in professional tennis - Breznik, K. (Journal of Sports Science & Medicine, 2013)
The aim of this study was to explore the effects of the gender variable in relation to other player and match characteristics on the advantage possessed by left-handed professional tennis players over their right-handed rivals. The data include 16 732 male tennis players and 16 432 female tennis players who played 438 937 and 415 346 matches, respectively, in the period from 1968 to the end of 2011. The results revealed that the advantage of left-handed professional tennis players is higher in males compared to females. The inverse impact of player and match quality on the left- handers' advantage was clearly confirmed. On the contrary, it seems that the type of court surface does not directly imply this advantage. To obtain an overview on the individual level, directed and weighted networks of tennis matches in both gender categories were constructed. Applying network analytic methods and the PageRank algorithm, the best left and right-handed players in the Open Era of tennis were identified. The top three ranked left-handed players in the male and female categories were found to be far more consistent in their ranks achieved against left and right-handed opponents compared to their right-handed counterparts